Stem Cells and Cancer - Majumder, Sadhan (Springer New York : Imprint: Springer, 2009)
Cancer is a major cause of human morbidity and mortality worldwide. Despite decades of basic and clinical research, the outcome for many cancer patients is still dismal. Although the existence of "stem-like" cells in cancer was hypothesized more than 150 years ago, recent discoveries have the potential to revolutionize cancer therapy. In particular, we now know that many cancers contain a fraction of self-renewing, drug- and radiation-resistant cells (cancer stem cells or cancer-initiating cells) and it is these cells-and not the major bulk of the tissue-that are the root cause for cancer initiation, relapse and metastasis. In a single volume, Stem Cells and Cancer offers up-to-date information about the role of stem cells in the development of normal and cancerous tissue, the mechanisms that differentiate normal from cancerous functions, and the use of these findings in developing mechanism-based therapies across all major types of cancer. It provides timely, cutting-edge information about cancer stem cells from the perspectives of both the basic and clinical sciences.